A review of Australia’s Mesozoic fishes - Berrell, Rodney; Boisvert, Catherine; Trinajstic, Kate; Siversson, M.; Alvarado-Ortega, J.; Cavin, L.; Salisbury, S.W.; Kemp, A. (TAYLOR & FRANCIS LTD, 2020)
© 2020 Geological Society of Australia Inc., Australasian Palaeontologists. The Australian Mesozoic fish fauna is considered to be depauperate in comparison with fish faunas in the Northern Hemisphere. However, due to its geographical location as a potential radiation center in the Southern Hemisphere, Australia’s Mesozoic fish fauna is important for understanding fish radiations. Most of the modern fish groups originated during the Mesozoic, but the first records of a modern fish fauna (freshwater and marine) in Australia does not occur until the lower Paleogene. Here, we review all known fossil fish-bearing localities from the Mesozoic of Australia, to improve the understanding of the record. The apparent low Australian Mesozoic fish diversity is likely due to its understudied status of the constituent fossils rather than to a depauperate record. In addition, we review recent work with the aim of placing the Australian Mesozoic fish fauna in a global context. We review the taxonomy of Australian fossil fishes and conclude that the assignments of many actinopterygians need major revision within a modern phylogenetic context. The vast majority of chondrichthyans are yet to be formally described; to the contrary all of the known lungfish specimens have been described. This study considers the microscopic and fragmented remains of Mesozoic fish already found in Australia, allowing a more complete view of the diversity of the fishes that once inhabited this continent.